Niche Tourism Markets – Means of Enhancing Sustainable Economic Development in EU's Eastern Periphery - Mara Ursache (CES Working Papers, 2015)
Within Europe, processes of economic convergence and divergence operate at various geographical scales, resulting in a very uneven geographical landscape. As mentioned in the international literature, the European economic space is characterized by a core-periphery structure. From this point of view, tourism has important significance since it is a noteworthy activity in the European Union and contributes to employment, income generation, overall development and economic rejuvenation of rural, peripheral or underdeveloped areas. There has been a shift in the nature of tourism demand driven by changes in consumption patterns, namely an increasing emphasis on more personalized or on specialized forms of tourist packages. This aspect required smaller and more flexible provision that created niche markets capable of providing peripheral areas the opportunity to capitalize on their comparative advantages associated with their natural environments, cultural heritage, and the role of local food in reinforcing personal identity and authenticity. The purpose of this study is to analyze EU's Eastern periphery (Bulgaria, Hungary, Poland, Romania and Slovakia) niche tourism markets potential and identify a few guiding principles that may lead to sustainable economic development.
Keywords: L83; O52; P52; 330; core – periphery; tourism; niche tourism markets; EU